Comparison study of four commercial SARS-CoV-2-rapid antigen tests - Jelen, Žiga (Strojniški vestnik, 2022)
During the corona virus (COVID-19) pandemic, there was a sharp increase in the need for diagnostic tests that could detect the presence of SARS-CoV-2 virus or its antibodies quickly and reliably. An important type in the group of diagnostic tests are rapid antigen lateral flow immuno-assay (LFIA) tests, which operate on the immuno-chromatographic principle with the lateral flow of analyte. Clinical practice in the last year has shown that such diagnostic tests can be effective in preventing the spread of the SARS-CoV-2 virus.The development, and, thus, the production of the rapid antigen LFIA tests, is influenced by a number of factors that determine their sensitivity and accuracy indirectly. These factors are directly dependent on the type of antibody produced, which is formed as an immune response when infected with the virus. The production of the rapid antigen LFIA tests is associated with the appropriate selection of basic components that determine the type and quality of these tests. The basic components include: substrates and membranes, antigens, antibody labels and compatible buffers. The correct choice of membranes and their materials is crucial to compiling an effective rapid antigen LFIA test. This study therefore presents a comparative analysis of four commercially available SARS-CoV-2-rapid LFIA tests using state-of-the-art characterisation techniques scanning electron microscopy (SEM), inductively coupled plasma-optical emission spectrometry (ICP-OES), environmental scanning electron microscope / energy-dispersive X-ray spectroscopy (ESEM/EDX), Fourier-transform infrared spectroscopy / attenuated total reflection (FTIR/ATR) for the individual components. The obtained results were the starting point for the development and assembling of our own rapid antigen LFIA test based on gold nanoparticles as antibody labels.
Keywords: analize; analysis; characterisation; components; hitri antigenski testi; karakterizacija; komponente; rapid antigen test